Sosialisasi Berbasis Masyarakat: Penerapan Progam Pengabdian dalam Mengatasi Tantangan Kenakalan Remaja dan Pernikahan Dini di Desa Poncokusumo - Fatihah, Zinniya; Fitriani, Devi Dwi; Anjali, Auliya' Ilmi; Pramaysheila, Rasya; Aulia, Jeny Fortuna Septi; Rifqi, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Poncokusumo Village faces serious challenges related to early marriage and juvenile delinquency. Student Work Lecture (KKM) UIN Maulana Malik Ibrahim Malang responded to this need by conducting outreach activities in Poncokusumo Village on Friday, January 19 2024. In this activity, information was presented regarding adolescent development, factors causing juvenile delinquency and early marriage, the impact juvenile delinquency and early marriage, as well as efforts to prevent juvenile delinquency and early marriage. Apart from that, there was also a question and answer session. Through socialization activities, it is hoped that teenagers can understand the negative impacts of this behavior and can be directed towards more positive choices. Long-term solutions require collaborative efforts from families, schools, and communities to create environments that support positive youth development.